Gambaran Kualitas Hidup Wartawan yang Meliput saat Pandemi COVID-19 - Penny Handayani; Katherine (Fakultas Psikologi Universitas Pancasila, 2021)
During a pandemic, unverified information spreads widely and rapidly. Therefore, accurate and fast information is needed. To get it, journalists must cover the field. work in the midst of a pandemic that affects the quality of life of journalists. When the quality of life of journalists decreases, the performance of journalists also decreases and affects the quality of information or news produced. Therefore, this study seeks to find out about the picture of the quality of life of journalists who cover the field during the COVID-19 pandemic in Indonesia. This research method is descriptive using 2 questionnaires, namely WHOQOL-BREF to measure the level of quality of life and COV19-QoL to measure the level of impact of the pandemic on quality of life. This study involving 167 participants found that journalists who covered the COVID-19 pandemic had a moderate level of quality of life in the domains of Physical, Psychological, and Environmental Health. While in the domain of Social Relations, the level of quality of life is relatively high. In addition, the results of this study indicate that the impact of the pandemic on the quality of life of journalists. The impact of covering the COVID-19 pandemic is moderate in the domains of General, Mental Health, Anxiety, and Depression. As for the domains of Physical Health and Personal Safety, the impact is high level.